INTRADURAL RUPTURE OF CERVICAL VERTEBRAL DISC - (:unkn) unknown (LIPPINCOTT-RAVEN PUBL, 1994)
Study Design. The authors discuss their experience with a patient who had cervical intradural disc herniation and relate the case to the relevant literature. Objectives. The patient was evaluated with direct radiographies, myelography, electromyography, and computerized tomography, as well as with neurologic examination. The follow-up period was 10 months post-operative. Summary of Background Data. Intradural disc herniation is a rare pathology nearly always confined to the lumbar region. In 1989, Katooka et al reviewed the existing literature and discovered 70 cases. Cervical intradural disc herniation, on the other hand, is much rarer, and there are only five cases in the literature. Methods. The patient's neurologic, neuroradiologic, and operative findings were evaluated and compared with the cases reported in the literature. Conclusions. The five patients in the literature had signs of cord compression, but the present patient is the first with root compression.